THE COMBAT DIARIES : TRUE STORIES FROM THE FRONTLINES OF WORLD WAR II - Guardia, Mike (Magnum Books, 2022)
World War II was the most destructive conflict in human history. At its peak, the US military drew some 16 million men into its ranks to defeat the Axis Powers. They came from nearly every walk of life-farmers, tradesmen, teachers, lawyers, professional athletes, and even Hollywood celebrities. But whether they came from the wheat fields of Kansas, the streets of New York, or the backlots of Tinseltown, these everyday heroes answered the call of duty when their country needed them. They were ordinary men who accomplished extraordinary things. Today, we call them the 'Greatest Generation'. The Combat Diaries is a collection of true stories from veterans who served on the frontlines during World War II